Regular Expression Recipes for Windows Developers A Problem-Solution Approach - Good, Nathan (Apress : Imprint: Apress, 2005)
Regular expressions are an essential part of programming, but they can be difficult to cope with. Enter Regular Expression Recipes for Windows Developers. This is the only book of its kind that presents material in a functional, concise manner. It contains over 100 of the most popular regular expressions, along with explanations of how to use each one. It also covers all of the major development languages, including JavaScript, VB, VB .NET, and C#. Author Nathan A. Good teaches by example and provides concise syntax references as necessary throughout the book. You're sure to find his examples accurate and relevant. This book is an ideal solutions guide for you to keep in a handy place for quick reference.